1997
DOI: 10.1074/jbc.272.39.24203
|View full text |Cite
|
Sign up to set email alerts
|

Cell Release of Bioactive Fibroblast Growth Factor 2 by Exon 6-encoded Sequence of Vascular Endothelial Growth Factor

Abstract: Vascular endothelial growth factor (VEGF) is a potent angiogenic factor which is synthesized and secreted by many differentiated cells in response to various stimuli including hypoxia and growth factor exposure. Alternative splicing of vascular endothelial growth factor mRNA results in three distinct molecular forms: V189 and V165 or V121 which lack the exons 6 or 6 and 7, respectively. To clarify the functions of the 24-amino acid insertion, the biological activity of V165 was compared with that exerted by pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 40 publications
1
44
0
2
Order By: Relevance
“…VEGF-induced tube formation by cultured bovine endothelial cells has been shown to be dependent upon bFGF (Jonca et al, 1997;Mandriota and Pepper, 1997). That study also revealed that the VEGF-dependence on bFGF is not via a decrease in VEGFR-2 (flk-1).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF-induced tube formation by cultured bovine endothelial cells has been shown to be dependent upon bFGF (Jonca et al, 1997;Mandriota and Pepper, 1997). That study also revealed that the VEGF-dependence on bFGF is not via a decrease in VEGFR-2 (flk-1).…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy might be explained by the fact that netrins have a strong affinity for heparan sulfates and thus may displace endogenous FGF-2 from its storage sites in the corneal stroma. We have previously noticed such a phenomenon for small peptides designed on the sequence of the exon 6 of VEGF 189 (26), which could induce a strong corneal angiogenesis despite binding to VEGF receptors in limbal endothelial cells. Recent evidence demonstrates that corneal vascularization relies on soluble VEGFR-1 expression (27), and it would be interesting to determine whether N1 or N4 could down-regulate VEGFR1 in the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…HUVEC and HUAEC from the same donors were cultured in EBM (Clonetics) supplemented with 10% FCS and 2 ng/ml VEGF every other day. Migration assay was performed as previously described (13,26) using recombinant VEGF, N1, and N4 (R & D Systems) as modulators. A total of 30,000 HUAEC were applied on the top of the Matrigel (BD Biosciences) on a 24-well plate and incubated at 37°C; 1 h later the modulators were added.…”
Section: Methodsmentioning
confidence: 99%
“…VEGF could also have an indirect effect by inducing the proliferation of endothelial cells, which themselves produce a number of growth factors. In addition, VEGF acts synergistically with fibroblast growth factor (FGF) (Hyder et al 2000), and it can release the angiogenic factor bFGF from its storage on heparan sulfates of the extracellular matrix (Jonca et al 1997), with the resulting combination of the two angiogenic mitogens having a synergistic effect on angiogenesis (Asahara et al 1995;Goto et al 1993). Further, the resulting availability of bFGF permits the expression of its mitogenic effect upon the smooth muscle cells.…”
Section: Growth Factors Identified In Fibroidsmentioning
confidence: 99%